Influenza vaccination coverage: findings from immunization information systems - Zimmerman, Laura A (BioMed Central, 2007)
BACKGROUND: Beginning with the 2004–05 influenza season, the Advisory Committee on Immunization Practices (ACIP) strengthened their existing encouragement that children aged 6–23 months receive influenza vaccination by creating a formal recommendation. METHODS: Well-functioning sentinel project immunization information systems (IIS) in Arizona (AIIS) and Michigan (MIIS) were used to calculate vaccination coverage among children aged 6–23 months during the 2004–05 influenza season. We calculated 2 measures of vaccination coverage: a) receipt of 1 or more doses of influenza vaccine September 2004-March 2005 and b) receipt of 2 or more doses (ie, fully vaccinated). We compared the dose administration distribution among children needing 1 and 2 doses and by provider type. Coverage by age and timeliness of vaccine doses entered into the IIS were also analyzed. RESULTS: Influenza vaccination coverage levels among children were 30% and 27% in AIIS and MIIS, respectively, for receipt of 1 or more doses; 13% and 11% of children, respectively, were fully vaccinated. Peaks in dose administration among children needing 1 and 2 doses were similar. There were differences in vaccine administration between public and private providers. Coverage was higher among younger children and over 75% of all influenza vaccine doses were entered into the IIS within 30 days after receipt of vaccine. CONCLUSION: Though almost 1/3 of children received 1 or more doses of vaccine in 2 IIS sentinel projects during the first season of the new recommendation, emphasis needs to be placed on increasing the proportion of children fully vaccinated. IIS data can be used for timely monitoring of vaccination coverage assessments.